Impact of Receivables Turnover and Collection Period on Manufacturing Profitability in Indonesia - Fenty Fauziah; Siti Rosa Lismawati; Nur Hanisfatin Rushami Zien (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The COVID-19 pandemic has profoundly disrupted the global economy, leading to unprecedented challenges and shifts in economic dynamics. Motivated by the economic disruptions caused by the COVID-19 pandemic, the research explores how these companies managed credit sales and collections amidst heightened financial instability. Employing a quantitative approach with panel data from 152 randomly selected firms, the study uses multiple linear regression analysis to assess the relationship between receivables turnover, average collection period, and profitability (measured by Return on Assets). Results reveal that receivables turnover has a significant positive effect on profitability, while the average collection period exerts a significant negative impact. Moreover, both variables jointly influence profitability, though their combined explanatory power is moderate. The findings highlight the importance of efficient receivables management in enhancing financial performance, especially during periods of economic volatility. Companies must prioritize efficient credit and collection policies to shorten the receivables cycle without sacrificing sales growth.